2014
DOI: 10.3390/toxins6010180
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Disorders in a Murine Model of Chronic Renal Failure

Abstract: Cardiovascular disease is highly prevalent in patients with chronic renal failure (CRF). However, data on the impact of CRF on the cerebral circulatory system are scarce—despite the fact that stroke is the third most common cause of cardiovascular death in people with CRF. In the present study, we examined the impact of CRF on behavior (anxiety), recognition and ischemic stroke severity in a well-defined murine model of CRF. We did not observe any significant increases between CRF mice and non-CRF mice in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…On the other hand, Fujisaki et al [16] did not reveal decrease in physical performance of CKD rats. In different study, CKD mice manifested decreased anxiety level presented as longer time spent in the light part of light/dark box [18]. Reasons leading to disparate results in different studies remain unclear, but might be on the account of different CKD stages of tested animals, which make them difficult to compare due to different approaches of determination of CKD severity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, Fujisaki et al [16] did not reveal decrease in physical performance of CKD rats. In different study, CKD mice manifested decreased anxiety level presented as longer time spent in the light part of light/dark box [18]. Reasons leading to disparate results in different studies remain unclear, but might be on the account of different CKD stages of tested animals, which make them difficult to compare due to different approaches of determination of CKD severity.…”
Section: Discussionmentioning
confidence: 97%
“…However, results of behavioral testing in CKD animals are scarce and controversial. Discrepancies may arise from use of different methods for CKD induction, e.g., surgery [19] vs. chemical induction potentially imposing additional toxicity [17], different time points of behavioral testing reflecting early or advanced stages of CKD [18,33], as well as variety of used behavioral tests. A comprehensive assessment of the behavioral changes during CKD in experimental animals is missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although depressive-like behavior was found in some animal models of CKD (21,32), it has been shown several times that animals with CKD exhibit decreased emotionality (39) and low-level anxiety (24,32,42). The anxiolytic effect of CKD was indicated mainly by reduced time spent in the dark chamber of light/dark box, while it was not manifested in other tests assessing anxiety, such as elevated plus maze or open field test (24,32,42). On the other hand, Kielstein et al (36) found increased anxiety-like behavior in 5/6nx rats when tested on hole board.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of neurological and behavioral phenotyping with renal function analysis can be of interest for several reasons. Neurological alterations can be secondary effects of renal dysfunction in both mice and men [30][31][32]. Several systemic diseases, like for example diabetes or excessive erythrocytosis [33,34], affect both neurological and renal function, and furthermore several genes and cellular mechanisms have been shown to be relevant in both systems [35][36][37][38].…”
Section: Kidney Functionmentioning
confidence: 99%